Khazanah Living Quran dalam Masyarakat Aceh - Muhammad Ridha (TAFSE: Journal of Qur'anic Studies, 2021)
The study of the Quran as a systematic effort towards matters related to the social phenomena of the Muslim community that responds to the Qur'an has been described since the time of the Prophet and his Companions. The emerging tradition is that the Quran is used as memorization (Tahfiz), sima '(listening), and study of Tafseer in addition to being an object of learning to various regions in the form of "Majlis Quran". This has become a treasure for Muslims. Over time, some more traditions and practices can bring the Qur'an to life. In this case, it would be interesting if we studied the living Quran through the people of Aceh. This can be a knowledge for people who do not know that Aceh has many treasures of traditions and practices through the living Quran. This can also be seen through the community's response to various practices covering the living Quran. This article examines the living Quran by examining the phenomena of living Quran practices that live in an Acehnese society in particular. Studi al-Qur’an merupakan sebuah upaya sistematis terhadap hal-hal yang terkait dengan fenomena sosial masyarakat muslim yang merespon al-Qur’an. Fenomena sosial tersebut sudah mulai sejak zaman Rasulullah dan para Sahabat. Tradisi yang muncul adalah al-Qur’an dijadikan dalam bentuk hafalan (Tahfiz), sima` (listening), dan kajian tafsir disamping sebagai obyek pembelajaran ke berbagai daerah dalam bentuk majlis al-Qur’an. Hal ini menjadi suatu khazanah bagi umat islam. Seiring berjalannya waktu, semakin bertambah tradisi maupun praktik yang mampu menghidupkan al-Qur’an. Dalam hal ini, akan jadi menarik jika kita mengulik living quran lewat masyarakat Aceh. Hal ini dapat menjadi suatu pengetahuan juga bagi masyarakat yang belum mengetahui bahwa Aceh memiliki segudang khazanah tradisi maupun praktik-praktik melalui living quran. Hal ini juga dapat dilihat melalui respon masyarakat baik dari segi macam-macam praktik yang meliput living quran. Serta mengkaji living quran dengan mengupas fenomena praktik living quran yang hidup di masyarakat Aceh khususnya.